2019
DOI: 10.1155/2019/4318306
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Factors of Extended-Spectrum Beta-Lactamases Producing Escherichia coli and Klebsiella pneumoniae Isolated from Cattle Farms and Raw Beef in North-West Province, South Africa

Abstract: Background. Extended spectrum beta-lactamases (ESBLs) producing Enterobacteriaceae cause severe infections in humans which leads to complicated diseases. There is increasing evidence that cattle contribute to the development and spread of multidrug resistant pathogens and this raises public health concern. Despite this, data on the concurrence of ESBL producing pathogens in cattle, especially in the North-West province are rare. Therefore, the aim of the present study was to isolate, identify and characterise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
32
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 44 publications
15
32
3
2
Order By: Relevance
“…In the present study, all our tested isolates were resistant to all βlactam antibiotics; these results were in accordance with the results of Caneiras et al, where 93.5% and 87.1% of their isolates were resistant to ceftazidime and cefotaxime respectively [23]. Similarly, Montso et al found that 66.7-100% of their isolates were resistant to β-lactams [24]. Moreover, our tested isolates showed 100% resistance to imipenim; in contrast, other studies showed that imipenim was one of the most effective antibiotics [25].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, all our tested isolates were resistant to all βlactam antibiotics; these results were in accordance with the results of Caneiras et al, where 93.5% and 87.1% of their isolates were resistant to ceftazidime and cefotaxime respectively [23]. Similarly, Montso et al found that 66.7-100% of their isolates were resistant to β-lactams [24]. Moreover, our tested isolates showed 100% resistance to imipenim; in contrast, other studies showed that imipenim was one of the most effective antibiotics [25].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings concurred with those reported elsewhere. [103][104][105][106][107] The high resistance of E. coli O157:H7, L. monocytogenes, and K. pneumoniae to tetracycline correlated to the extensive use of tetracycline in dairy farms for treatment of infectious diseases. 108 In the current study, all strains had a MAR index which ranged between 0.44-0.88, since it is well known that isolates which display a MAR index less than 0.2 are supposed to come from antibiotic-rare used sources.…”
Section: Discussionmentioning
confidence: 99%
“…This is the rst study reporting the genetic diversity of carbapenem-resistant E. coli strains isolated from different environmental sources in the Eastern Cape Province, with other studies by Montso et al [78] and Chukwu et al [79] reporting on the genotypic diversity of E. coli isolates recovered from farms and water samples respectively both in the North West Province.…”
Section: Discussionmentioning
confidence: 68%